[Stammbuch Theagen ...] - Dorothea,Lieber, Johann Christian,Petz, Leopold,Schultze, Franziska (print, 1803)
Beschreibung: Stammbuch einer jungen Dame, die in einigen Eintragungen mit
Einband: Roter Pappeinband in grünem Schuber